ABOUT THE METHOD OF DYNAMIC PROGRAMMING PROCESS OF INTEGRATED HOUSING MODERNIZATION - S. H. Bayramukov; Z. N. Dolaeva; A. O. Omarov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
This article analyzes the problem of housing renewal. Permission more abstract and extensive understanding of the concept of modernization as the integrated development of residential real estate. The mathematical model of optimization of the repair work using methods of dynamic programming.